AAV-9 mediated phosphatase-1 inhibitor-1 overexpression improves cardiac contractility in unchallenged mice but is deleterious in pressure-overload - Schwab, Dominic Mathias; Tilemann, Lisa; Bauer, Ralf; Heckmann, Markus B.; Jungmann, Andreas; Wagner, M.; Burgis, J.; Vettel, Christiane; Katus, Hugo; El-Armouche, A.; Müller, Oliver J. (Gene therapy, 2018)
The downregulation of β-adrenergic receptors (β-AR) and decreased cAMP-dependent protein kinase activity in failing hearts results in decreased phosphorylation and inactivation of phosphatase-inhibitor-1 (I-1), a distal amplifier element of β-adrenergic signaling, leading to increased protein phosphatase 1 activity and dephosphorylation of key phosphoproteins, including phospholamban. Downregulated and hypophosphorylated I-1 likely contributes to β-AR desensitization; therefore its modulation is a promising approach in heart failure treatment. Aim of our study was to assess the effects of adeno-associated virus serotype 9 (AAV9) - mediated cardiac-specific expression of constitutively active inhibitor-1 (I-1c) and to investigate whether I-1c is able to attenuate the development of heart failure in mice subjected to transverse aortic constriction (TAC). 6-8 week old C57BL/6 N wild-type mice were subjected to banding of the transverse aorta (TAC). Two days later 2.8 × 1012 AAV-9 vector particles harbouring I-1c cDNA under transcriptional control of a human troponin T-promoter (AAV9/I-1c) were intravenously injected into the tail vein of these mice (n=12). AAV9 containing a Renilla luciferase reporter (AAV9/hRluc) was used as a control vector (n=12). Echocardiographic analyses were performed weekly to evaluate cardiac morphology and function. 4 weeks after TAC pressure- volume measurements were performed and animals were sacrificed for histological and molecular analyses. Both groups exhibited progressive contractile dysfunction and myocardial remodeling. Surprisingly, echocardiographic assessment and histological analyses showed significantly increased left ventricular hypertrophy in AAV9/I-1c treated mice compared to AAV9/hRluc treated controls as well as reduced contractility. Pressure-volume loops revealed significantly impaired contractility after AAV9/I-1c treatment. At the molecular level, hearts of AAV9/I-1c treated TAC mice showed a hyperphosphorylation of the SR Ca2+-ATPase inhibitor phospholamban. In contrast, expression of AAV9/I-1c in unchallenged animals resulted in selective enhancement of phospholamban phosphorylation and augmented cardiac contractility. Our data suggest that AAV9-mediated cardiac-specific overexpression of I-1c, previously associated with enhanced calcium cycling, improves cardiac contractile function in unchallenged animals but failed to protect against cardiac remodeling induced by hemodynamic stress questioning the use of I-1c as a potential strategy to treat heart failure in conditions with increased afterload.
Advance online publication, 8 February 2018
Gesehen am 02.09.2019